ANALISIS LITERASI DIGITAL GURU MATEMATIKA MTSN 1 KUTAI KARTANEGARA - Untu, Zainuddin; Faradisa, Irsya; Sugeng, Sugeng (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
This study aims to determine the digital literacy of MTsN 1 Kutai Kartanegara mathematics teachers in preparing questions in mathematics learning. This research is a descriptive qualitative research. The subjects of this research are mathematics teachers including VII, VIII, and IX grade teachers at the school. The object of this research is the digital literacy of mathematics teachers. Data were collected through questionnaires, interviews, and documentation. Data analysis in this study was carried out using three stages, which are data reduction, data presentation, and conclusion drawing. The results showed that the digital literacy of mathematics teachers at MTsN 1 Kutai Kartanegara was categorized as capable in preparing questions in mathematics learning. In terms of teacher capabilities, they are capable in aspects of internet searching, content evaluation, and knowledge assembly. Although, in the aspect of hypertextual navigation they are still less capable